2015
DOI: 10.1038/srep08089
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale simulation of shale transport properties using the lattice Boltzmann method: permeability and diffusivity

Abstract: Porous structures of shales are reconstructed using the markov chain monte carlo (MCMC) method based on scanning electron microscopy (SEM) images of shale samples from Sichuan Basin, China. Characterization analysis of the reconstructed shales is performed, including porosity, pore size distribution, specific surface area and pore connectivity. The lattice Boltzmann method (LBM) is adopted to simulate fluid flow and Knudsen diffusion within the reconstructed shales. Simulation results reveal that the tortuosit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
196
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 242 publications
(203 citation statements)
references
References 51 publications
7
196
0
Order By: Relevance
“…The results indicated that Knudsen diffusion occupies an important proportion in the shale gas transport. 24 Zhang et al developed a pore network model to simulate the gas flow regimes. They found that slip flow and Knudsen diffusion are strengthened while viscous flow is weakened with the decrease of pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that Knudsen diffusion occupies an important proportion in the shale gas transport. 24 Zhang et al developed a pore network model to simulate the gas flow regimes. They found that slip flow and Knudsen diffusion are strengthened while viscous flow is weakened with the decrease of pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Models of the first category used in previous studies only considered the Darcy and partial non-Darcy effects Chen et al 2015). Pore-scale modelling of shale gas flow with LBM is still conducted in a capillary (Zhang et al 2014) and is incipient when applied to 3D complex porous spaces.…”
Section: Pore Network Model: Ab Modelmentioning
confidence: 99%
“…Ma et al (2014) extracted pore networks from reconstructed 3D images and, together with the similar non-Darcy flux formula, used them to examine the effect of TMAC (a parameter relates to slip effect) and the overall scaling of the throat size on the apparent permeability. Chen et al (2015) performed LBM simulations using reconstructed 3D images of several shale samples and only calculated the absolute permeability and diffusivity on the pore scale. On the sample scale, a modified dusty gas model (DGM) that combines the effects of slippage and Knudsen diffusion were used to derive the correlation factor of the apparent permeability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, building a pore network model for 3D flow simulations in heterogeneous fine-grained rocks is an unresolved issue. Some approaches extract 3D pore data directly from FIB-SEM [31] or use the Markov chain Monte Carlo (MCMC) reconstruction method on 2D images [32,33]. Whether these complex pore network models are representative for the sample is another uncertainty [17,31,34].…”
Section: Introductionmentioning
confidence: 99%